The impact of the strengthened personal data protection regulation on users' privacy concerns - Sangjun Nam; Youngsun Kwon (International Telecommunications Society (ITS), 2024)
Considering that privacy concerns could affect users' privacy behavior as an antecedent, it is important to investigate the impact of strengthened personal data protection regulation on users' privacy concerns. However, there exists mixed views that the personal data protection regulation has a positive or negative effect on users' privacy concerns by increasing privacy awareness and trustworthiness, respectively. We propose the approach using smartphone platform-level privacy regulation as a proxy for national-level personal data protection regulation to overcome the difficulty of setting up treatment and control groups for implementing dynamic Difference-in-Difference analysis. The result showed that introducing personal data protection regulation has a positive effect on users' privacy concerns in the short term; however, the positive effect could be diluted over time.
Keywords: 330; Personal Data; Online Platform; Regulation; Privacy Concern; App Tracking Transparency